Rapid spread of a new alien and potentially invasive species, Clathrocaspia knipowitschii (Makarov, 1938) (Gastropoda: Hydrobiidae), in the Danube River - Szekeres, József; Beermann, Arne; Neubauer, Thomas A.; Očadlík, Miroslav; Paunović, Momir; Raković, Maja; Csányi, Béla; Varga, András; Weigand, Alexander; Wilke, Thomas; Fehér, Zoltán (Archives of Biological Sciences, 2022)
Paper description: The non-indigenous freshwater snail Clathrocaspia knipowitschii was detected in the Danube River for the first time in 2013. Since then, the snail has spread along the Danube The identity of the species revealed by morphological characters is confirmed by DNA barcoding. DNA metabarcoding of bulk samples proved effective in unravelling the distribution of this gastropod. It is necessary to monitor systematically the occurrence and spread of alien species in aquatic ecosystems. Abstract: The distribution and spread of a new alien gastropod species, Clathrocaspia knipowitschii (Makarov, 1938) (Gastropoda: Hydrobiidae: Caspiinae) in the Danube River was examined. First findings of this species for Hungary, Slovakia, Romania, Bulgaria and Serbia are presented. Clathrocaspia knipowitschii was initially found in 2013 in the Iron Gate stretch of the Danube River at the border between Romania and Serbia. In 2019 and 2020, the species was found at several sites in the lower Danube in Romania, Serbia and Bulgaria, and also upstream in the middle Hungarian Danube in high population densities. The species appears to have spread along more than 800 km in six years. This finding together with the available abundance data indicates that C. knipowitschii is potentially an invasive species, but further observations are needed.